EMBEDDING THE CONCEPT OF PATHOCENOSIS INTO A MULTI-DIMENSIONAL HEALTHCARE MODEL FOR A GLOBAL PERSPECTIVE OF THE HEALTH SCENARIO IN THE 21ST CENTURY - Sethuraman KR (Asian Journal of Medicine & Health Sciences, 2020)
The 21st Century physicians need awareness of the complex linkages between human activities and global health risks resulting from pollution, climate change, and disease outbreaks due to emerging and re-emerging infections. Pathocenosis and anthropocenosis conceptualise these complex linkage. A multi-dimensional healthcare model extends the conventional doctor-patient interaction to include the various factors and linkages, which greatly influence the process and the outcome. A qualitative pilot study among medical interns and resident revealed that the model helped them to go beyond the traditional case based approach to view the individual healthcare problems from a global and holistic perspective.